(3JbfjI GdHUeI GdhQGKjI aj GdcTa Yf GdLQGFe (B/ s - (3eMeO eMehO GdTfGhjs; (3YeQ eMeO SGde (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2009)
(3GYJeO GdHGMK ai OQGSJg GdSGHbI Ydi GdGSJbQGA hGdJMdjd hGdebGQfI eSJNOeG GdefgL GdJGQjNi hGdhUai hGdJMdjdi hbO JhUd GdHGMK Edi LhGR GdCNP HfJGFL GdHUeI GdhQGKjI ai EKHGJ LQGFe GdbJd gh GdCbQH Edi JMbjb GdYOd Hjf GdfGS hCf JaYjdg VeGfI ddMO ef GdLQjeI ai YUQ cKQJ ajg hJYbOJ ceG jLhR GYJeGO fJGFL GdHUeI GdhQGKjI ai EKHGJ LQGFe GdRfG hGdGZJUGH hGdSQbI hGdbJd hGdJYRjQ eY VQhQI hVY VhGHW dGSJNOGe GdHUeI GdhQGKjI hJJeKd gPg GdVhGHW ai YOe GdeNGdaI debGUO GdTQY hYOe GdeYGQVI deG KHJ HGdfU Ch GdELeGY hYOe EMdGd GdHUeI GdhQGKjI eMd eGCKHJg GdTQY ef hSGFd s
(3jTJed Ydi edGMbs
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2009.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdHUeI GdhQGKjIs; (3GdEKHGJ GdLfGFj s; (3EKHGJ LQGFe GdbJd s; (3EKHGJ GdfSHs; (3EKHGJ LQGFe GdbJds; (3EKHGJ LQjeI GdSQbIs; (3GSJNOGe GdHUeI GdhQGKjIs; (3GdehGO GdHjhdhLjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs